Rules of deception - Reich, Christopher (New York Anchor books, 2009)
Following the death of his wife in a mountaineering accident, Dr. Jonathan Ransom receives a mysterious message that makes him the subject of an international manhunt as he struggles to unravel the truth behind his wife's secrets
Keywords: Physicians -- Fiction; Terrorism -- Fiction; Wives -- Crimes against -- Fiction; Switzerland -- Fiction